Exploration and Practice of Teaching “Engineering Ethic” for Professional Degree Graduate Students Under the Background of “New Engineering” - He, Wei; Cao, Jianshu; Zhao, Jing (Advances in Social Sciences Research Journal, 2023)
Under the background of new engineering and curriculum ideological and political construction, the ethics education of engineering ethics courses for engineering graduate students must be constantly explored and tried. Based on the actual situation of the training of professional degree graduate students in our university, this paper starts from various aspects such as teaching content, teaching methods, textbook cases and comprehensive assessment. This paper probes into the course construction and teaching reform of engineering ethics for engineering graduate students, and explores the mode of engineering ethics education which adapts to the needs of our country’s own development.